Experimental Behavior of One-Way RC Ultra-Thin Slabs Retrofitted with Post-Installed NSM CFRP Rods - Al-Nussairi, Alaa N.A.; S.H. Suwaed, Ahmed (Journal of Composites and Biodegradable Polymers, 2025)
This study evaluates the flexural behavior of ultra-thin (50 mm) one‑way reinforced‑concrete (RC) slabs retrofitted with near‑surface mounted (NSM) carbon‑fiber‑reinforced polymer (CFRP) rods under quasi‑static loading. T300‑grade CFRP rods (≈4 mm diameter) were bonded in pre‑cut 7 mm × 7 mm grooves using a two‑part epoxy. As a proof-of-concept experimental baseline, three simply‑supported specimens (1000 mm × 500 mm × 50 mm) were tested in a six‑point bending configuration (four applied loads + two reactions): two conventional controls and one strengthened slab. A load‑control rate of ~15 kN/min was applied; the controls were cycled twice and the strengthened slab four times. Relative to the average of the two control specimens, the strengthened slab achieved ~+103% ultimate load (49.4 kN vs 24.3 kN) with a ~24% reduction in ductility (μΔ = 2.4 vs 3.15). Hysteretic dissipation, computed as loop area per cycle, was markedly higher for the strengthened slab; cycle‑matched comparisons (cycles 1–2) are reported alongside cumulative values. The results show that NSM CFRP can markedly enhance capacity and energy absorption of very thin one‑way slabs, with a trade‑off in ductility that should be considered in design.